AYURVEDIC MANAGEMENT OF PSORIASIS - A CASE STUDY - Gameti, *Rahul; Kori, V.K.; Patel, Kalpana S.; Rajagopalas, S. (International Journal of Ayurveda and Pharma Research, 2016)
In Ayurveda, all types of skin diseases are described under one umbrella term of Kushtha. Acharyas have described that all Kushthas have Tridosha involvement but the type of Kushtha depends on the predominance of particular Doshas. Eka Kushtha is compared with psoriasis due to its maximum resemblance. Psoriasis is a long-lasting autoimmune disease characterized by patches of abnormal skin. These skin patches are typically red, itchy, and scaly. They may vary in severity from small and localized to extensive, large and spread in complete body. It typically presents with red patches and white scales on the top. Areas of the body most commonly affected are the back of the forearms, shins, around the navel, and the scalp. Psoriasis is generally thought to be a genetic disease which is triggered by environmental factors. Other factors such as local trauma, general illness and stress are also involved. In modern medicine, the cure of this disease is out of question as the cause is unknown. Ayurveda propounds a holistic treatment approach for psoriasis. As per Ayurvedic view point Vata, Pitta and Kapha vitiation are the major contributing pathological factors in the body. The line of treatment of skin diseases are Shodhana and Shamana therapy. Virechana Karma (purgation therapy) followed by internal medications are considered as the best line of management for skin disorders. A case report of 13 year old male child presented with well demarcated raised red scaling silvery patches on trunk and back region, limbs with itching and burning will be presented in the full paper.